Exploring students’ preferences between online corrective feedback and direct corrective feedback(face-to-face) in writing class in tertiary education / Nazifah Hamidun, Nur Ilianis Adnan and Berlian Nur Morat - Hamidun, Nazifah; Adnan, Nur Ilianis; Nur, Berlian (2023)
Feedback is crucial to be provided in students’ learning process especially in writing skill. Nevertheless, the method of providing feedback is valued differently by students. This study sought to explore the students’ preferences at tertiary education between the online corrective feedback and direct corrective feedback (face-to-face) in writing class. The study used a qualitative research design which was participated in by 67 participants from a technical university. Data from an open-ended survey questionnaire on student’s preferences of obtaining feedback were collected from the participants who were pursuing an English academic course at the tertiary level. The most preferred feedback strategy was direct corrective feedback (face-to-face) which facilitated the students to enhance their writing skills. Thus, the results indicated that direct corrective feedback (face-to-face) was crucial and effective to assist the students in their writing. The results of this study have important implications for tertiary level students and instructors. The students’ expectations and preferences must be acknowledged to support them in language teaching and learning.